KIE Yang Service Excellent Pada Ibu Hamil Tentang Hiperemesis Gravidarum Di Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang Tahun 2022 - Anna Waris Nainggolan; Friza Novita Sari Situmorang; Sonia Novita Sari; Ribur Sinaga; Imarina Tarigan (Jurnal Kabar Masyarakat, 2023)
Hyperemesis Gravidarum in pregnant women in the VII hamlet of Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency will still experience a significant increase in 2023. Therefore, it is necessary to provide Information and Education Communication (IEC) to pregnant women about Hyperemesis Gravidarum. This activity was carried out with the aim of providing education through leaflets to pregnant women in all trimesters about Hyperemesis Gravidarum. And motivate pregnant women to continue to apply the prevention and treatment of Hyperemesis Gravidarum during pregnancy. The method used uses two stages, namely the implementation and evaluation stages. The results of the process evaluation related to the management of hyperemesis Gravidarum in pregnant women are in accordance with the existing standard operating procedures and recommendations from the Indonesian Ministry of Health. The health education provided was in accordance with SOPs, but several health workers had not emphasized IEC regarding the prohibition of taking anti-nausea drugs at random without a doctor's prescription. Educational media innovations have not varied and have not described in detail the handling of hyperemesis gravidarum during pregnancy, especially how to consume the correct portion of food while experiencing hyperemesis gravidarum. The results of the output evaluation related to the management of hyperemesis gravidarum in pregnant women are appropriate. There is an increase in the knowledge and skills of post-training health workers. Post-counseling evaluation is carried out depending on free time and the number of patients visiting.